Study on Mechanical Law of Vibration Abscission of Camellia Oleifera Fruit Based on High-Speed Camera Technology (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
The movement and mechanical characteristics of oil-tea camellia fruit coupling with flower simultaneously during the harvest period were studied to provide an indispensable theoretical guideline for the mechanized picking machine. The mechanical properties of Camellia oleifera were obtained by investigating its flowers and fruits, and the vibration harvesting of Camellia oleifera was studied by using dynamic vibration device. The i-Speed3 high-speed camera was used to record the harvesting process, and the image analysis and calculation were carried out by its own Control-Pro software. The results showed that different varieties of Camellia oleifera had different flowering periods, ranging from 30 to 55 days; their weight also varied among varieties; there was no inevitable relationship between the binding force (pulling force and torque) of fruit stalks and their varieties, locations and diameter of fruit stalks. More importantly, during the vibration process, the fruit peeling speed is related to the vibration source clamping position and vibration parameters. Under the condition of short clamping distance and high frequency and low amplitude, the fruit is more likely to fall off.